2005
DOI: 10.1074/jbc.m401394200
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-Cytoplasmic Shuttling of the Oncogenic Mouse UNP/USP4 Deubiquitylating Enzyme

Abstract: The oncogenic deubiquitylating enzyme (DUB) Unp/ Usp4, which binds to the retinoblastoma family of tumor suppressor proteins, was originally described as a nuclear protein. However, more recent studies have shown it to be cytoplasmic. In addition, analysis of its subcellular localization has been complicated by the existence of the paralog Usp15. In this study, we resolved this controversy by investigating the localization of exogenously expressed Usp4 (using red fluorescent proteinUsp4) and of endogenous Usp4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…The ratio of nuclear-to-cytosolic distribution is dependent on the cell type (Soboleva et al, 2005). The data shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The ratio of nuclear-to-cytosolic distribution is dependent on the cell type (Soboleva et al, 2005). The data shown in Fig.…”
Section: Resultsmentioning
confidence: 80%
“…hUSP15 was observed both in the cytoplasm of NIH3T3 and HeLa cells as well as in HeLa nucleoli (33). Only recently, hUSP15 has been found to co-purify with the human COP9 signalosome (CSN) complex (11) and suggested to be the human homolog of the Saccharomyces pombe Ubp12 protein that regulates the activity of CSN-associated cullin-RING ubiquitin ligases (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise the three isoforms that retain the catalytic domain are identical. They also retain predicted nuclear export signals (NES) (Soboleva et al, 2005) and, by homology with rat, a functional nuclear localisation signal (NLS) (Park et al, 2000).…”
Section: Descriptionmentioning
confidence: 99%
“…Rat UBP109 localises to both the cytoplasm and the nuclear compartment, with the latter dependent on a C-terminal NLS (Park et al, 2000) that is conserved across species. Using an Usp15/USP15-specific polyclonal antibody, Soboleva et al demonstrated that in HeLa (human cervical cancer cells) endogenous USP15 localised to the cytoplasm and nucleolus, but was largely excluded from the nucleoplasm; whilst in NIH3T3 (mouse fibroblast cells), Usp15 localised in the cytoplasm and was enriched proximal to the plasma membrane (Soboleva et al, 2005). Interestingly, GFP-tagged USP15 (isoform USP15-203) adopts a largely cytoplasmic distribution in human cancer cell lines (Urbé, unpublished observation).…”
Section: Localisationmentioning
confidence: 99%